Genome-wide analysis reveals regulatory role of G4 DNA in gene transcription - Du, Zhuo; Zhao, Yiqiang; Li, Ning (Genome Research, 2007)
G-quadruplex or G4 DNA, a four-stranded DNA structure formed in G-rich sequences, has been hypothesized to be a structural motif involved in gene regulation. In this study, we examined the regulatory role of potential G4 DNA motifs (PG4Ms) located in the putative transcriptional regulatory region (TRR, –500 to +500) of genes across the human genome. We found that PG4Ms in the 500-bp region downstream of the annotated transcription start site (TSS; PG4MD500) are associated with gene expression. Generally, PG4MD500-positive genes are expressed at higher levels than PG4MD500-negative genes, and an increased number of PG4MD500 provides a cumulative effect. This observation was validated by controlling for attributes, including gene family, function, and promoter similarity. We also observed an asymmetric pattern of PG4MD500 distribution between strands, whereby the frequency of PG4MD500 in the coding strand is generally higher than that in the template strand. Further analysis showed that the presence of PG4MD500 and its strand asymmetry are associated with significant enrichment of RNAP II at the putative TRR. On the basis of these results, we propose a model of G4 DNA-mediated stimulation of transcription with the hypothesis that PG4MD500 contributes to gene transcription by maintaining the DNA in an open conformation, while the asymmetric distribution of PG4MD500 considerably reduces the probability of blocking the progression of the RNA polymerase complex on the template strand. Our findings provide a comprehensive view of the regulatory function of G4 DNA in gene transcription.
10.1101/gr.6905408